A decision support system using Neurofuzzy algorithm methods in selecting lecturer's teaching work load for bachelor in multimedia / Asmaa Musa - Musa, Asmaa (2007)
A large nimiber of techniques, such as Neurofuzzy algorithm methods are used to produce an efficient and effective system. A key stage in the system process is the selection of features. This paper discuss about a decision support system using Neurofuzzy algorithm methods in selecting lecturer's teaching work load for Bachelor in Multimedia. The prototype of this project is design based on Neurofuzzy algorithm method. Decision support system is a system for making decisions. A decision is a choice between alternatives based on estimates of the values of those alternatives. Supporting a decision means supporting this choice by supporting the estimation, the evaluation and the comparison and choice Neurofuzzy controller works similar to a conventional system; it accepts an input value, performs some calculations, and generates an output value. There are three steps in designing Neurofuzzy algorithm method. The first step is to understand the physical system, its control requirements and identifies the controller's inputs and outputs. Secondly, to define the ranges and labels for the membership functions and describe the controller's operation using fuzzy rules. Finally, to debug and tune the controller by modifying membership functions, or rules, whenever appropriate